Design of Integration of Religion and Science in Handling Covid-19 Perspective of Ismail Raji Al Faruqi's Thought - Hannan, Abd. (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
In the last two years, there has been a lot of discussion about the integration of religion and science. The discussion emerged as a response to the split in the logic of religious and scientific thinking regarding the handling of COVID-19. By conducting research based on qualitative methods and in-depth analysis through the theory of Islamization of science, this study found two findings; First, The religion-science polarization in the dynamics of dealing with COVID-19 is reflected in the selfishness of the two in responding to COVID-19. The orthodox religious perspective tends to be metaphysical-dogmatize, while science tends to be positivistic-empirical; Second, Al-Faruqi's idea of ​​Islamization of science emphasizes the five principles of unity (tawhid), namely the unity of God, creation, truth-knowledge, humanity, and the unity of life. In the context of dealing with COVID-19, the five units cover two dimensions; 1) Methodology, a dimension that specifically targets religious areas to be more transformative and not fatalistic; 2) Content, dimensions related to the world of science so as not to be trapped in the view of secular positivism.